Long-Term Effects of COVID-19: A Guide to Post-Recovery Symptoms in Diyala Governorate, Eastern Iraq : Long-Term Effects of COVID-19...... - sarmad Mohammad (Hasanuddin University, 2023)
Background: The COVID-19 pandemic is a massive global event with significant health, psychological and social consequences, appeared for the first time in December 2019, it was officially called Severe Acute Respiratory Syndrome (SARS-Cov-2), it causes important diseases in humans ranging from common cold to deadly respiratory infections, most infected people recovering within a few weeks, except some of them, have symptoms for a long time and it is called a post-COVID-19 syndrome. Objectives: This study was conducted in Diyala Governorate, north of Baghdad, from October 2022 to March 2023, to investigate the most important symptoms that people are still suffering from them after recovering from COVID-19. Materials and methods: The study was carried out by cross-sectional analysis of a sample of people who had previously been infected with COVID-19, using a questionnaire that was divided into several sections including demographic details for the participants in this study, duration of hospitalization, and the symptoms that still accompany them after gaining full recovery from infection with the virus. The sample size was 300 individuals. Results: The current study concluded that many of the symptoms are still associated with people who recovered after infection with Covid-19. The following symptoms were most common, fatigue after any slight exertion, headache, Dizziness when standing, coughing, and difficulty breathing with proportions of 70.0%, 69.0%, 64.0%, 60.7%, and 55.7%, respectively. there were highly significant differences in the age of the sample, with the highest age group (10-40) accounting for 85%, while the lowest age group (>60) also there was statistically significant differences between age and rate of symptoms appearing, as the symptoms are more common in male from the female. no significant differences between the samples on the rural versus urban housing variable and oxygen demand during the hospital stay. Conclusion: After full recovery, COVID-19 continues to produce major complications, with males being more affected than females.